Validating the performance of 3 sepsis screening tools in patients with clinical chorioamnionitisAJOG Global Reports at a Glance - Fadi B. Yahya, MD, MHA; Mohammed Yousufuddin, MD; Heidi J. Gaston, MD; Eniola Fagbongbe, MD; Laureano J. Rangel Latuche, MS (Elsevier, 2023)
BACKGROUND: Maternal sepsis is a leading cause of maternal death in the United States. Approximately two-thirds of maternal deaths because of sepsis are related to delayed recognition or treatment. New early warning systems using a 2-step approach have been developed for the early recognition of sepsis in obstetrics; however, their performance has not been validated. OBJECTIVE: This study aimed to assess the performance of 3 primary screening tools introduced by the Society of Obstetric Medicine Australia and New Zealand and the California Maternal Quality Care Collaborative for use in the first step of their 2-step early warning systems. The obstetrically modified quick Sequential (sepsis-related) Organ Failure Assessment score tool, the obstetrically modified Systemic Inflammatory Response Syndrome tool, and the obstetrically modified Systemic Inflammatory Response Syndrome 1 tool were evaluated for the early detection of sepsis in patients with clinically diagnosed chorioamnionitis. STUDY DESIGN: This was a retrospective cohort study using prospectively collected clinical data at a tertiary care center and an affiliated healthcare system. The electronic health records were searched to identify and verify cases with clinically diagnosed chorioamnionitis between November 2017 and September 2022. The flow sheet for every patient was reviewed to determine when criteria were met for any of the 3 tools. The performance of these tools was analyzed using their sensitivity, specificity, positive and negative predictive values, and receiver operating characteristic curve for the identification of sepsis. RESULTS: There were 545 cases that had the requisite data for inclusion in the analysis. Of note, 11 patients met the criteria for sepsis. Both the obstetrically modified Systemic Inflammatory Response Syndrome and obstetrically modified Systemic Inflammatory Response Syndrome 1 tools had overall similar test characteristics, which were notably different from the obstetrically modified quick Sequential Organ Failure Assessment tool. The screen-positive rate of the obstetrically modified quick Sequential Organ Failure Assessment tool (1.5%; 95% confidence interval, 0.6%-2.9%) was lower than that of the obstetrically modified Systemic Inflammatory Response Syndrome tool (60.0%; 95% confidence interval, 55.7%-64.1%) and the obstetrically modified Systemic Inflammatory Response Syndrome 1 tool (50.0%; 95% confidence interval, 45.8%-54.3%). The sensitivities of the obstetrically modified Systemic Inflammatory Response Syndrome tool (100.0%; 95% confidence interval, 71.5%-100.0%) and the obstetrically modified Systemic Inflammatory Response Syndrome 1 tool (100.0%; 95% confidence interval, 71.5%-100.0%) were higher than that of the obstetrically modified quick Sequential Organ Failure Assessment tool (18.0%; 95% confidence interval, 2.3%-51.8%). All 3 tools had high negative predictive values; however, their positive predictive values were poor. CONCLUSION: This study demonstrated that all 3 tools had limitations in screening for sepsis among patients with a clinical diagnosis of chorioamnionitis. The obstetrically modified quick Sequential Organ Failure Assessment tool missed more than half of the sepsis cases and, thus, had poor performance as a primary screening tool for sepsis. Both the obstetrically modified Systemic Inflammatory Response Syndrome and obstetrically modified Systemic Inflammatory Response Syndrome 1 tools captured all sepsis cases; however, they tended to overdetect sepsis.